Microbial quality of mung bean (Vigna radiata, Linn) sprouts from Makati and Taguig, Philippines - Estrada, Ana Marie Pidlaoan (2005)
ABSTRACT This study determined the microbial quality of mung bean sprouts vended in selected wet markets in Makati and Taguig cities, Philippines. Sprout production, handling, transportation and vending practices of sprout vendors and producers were documented. The microbial quality parameters included total plate count (TPC), lactic acid bacteria (LAB) counts, yeast and mold counts (YMC), total coliform (TCC), generic E. coli counts (GEC) and Salmonella spp. The thermal inactivation of Salmonella typhimurium E1366 in cooked mung bean sprouts was also established. Results showed that samples had TPCs in the range of 5.93-8.31 log10 cfu/g, LAB counts of 5.67-8.49 log10 cfu/g, YMCs of <1.00-1.15 log10 cfu/g, TCCs of 6.82-7.49 log10 cfu/g and GEC of <4.00-5.09 log10 cfu/g. Salmonella spp. was detected in all the samples. The established D-values of S. typhimurium E1366 in cooked mung bean sprouts were 0.28, 0.28 and 0.12 min at 60, 70 and 90°C, respectively.